Mgoduyanuka: faunal remains - Plug, I.; Brown, A. (Southern African Humanities, 2021)
Faunal remains from the Later Iron Age site of Mgoduyanuka reflect a community which was heavily dependent on herding to obtain meat. Hunting and fishing were probably regarded as forms of recreation.